(3OQGSI hTQM RhGFO eSGFd GdLGgdjI ddYdGeI GdeMOK YHO Gddg Hf eMeO Hf CMeO GdOhjT (B/s - (3GdjhSa, gjdI HfJ Vja Gddg Hf ZGfes; (3GdOhjT, YHO Gddg Hf eMeO Hf CMeOs 1373-1409 (3gLQjs ((3GdQjGV (B:s (3OGQ GdYGUeI ddfTQ hGdJhRjY ,s, 2010)
(3aj GdYbjOI hGdePGgH GdeYGUQI(B.s
(3GdCUd CWQhMI eGLSJjQ(B-(3LGeYI GdEeGe eMeO Hf SYhO GdESdGejI, (B1428 (3g`(B.s
Keywords: (3Yde GdcdGes -- (3JhMjOs; (3GdHOY aj GdESdGes; (3YbjOIs